ESTUDO DO PERFIL LIPÍDICO DE MULHERES PÓS-MENOPAUSA DE MUNICÍPIO DO INTERIOR DO ESTADO DO RIO GRANDE DO SUL - Pletsch, Marilei U.; Oliveira, Karla R. d.; Kal, Jerry B.; Foellmer, Lilian; Berlezi, Evelise d. M. (Salão do Conhecimento, 2013)
Resumo